2018
DOI: 10.3390/app8101927
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approach to Dysphonia Detection

Abstract: This paper addresses the processing of speech data and their utilization in a decision support system. The main aim of this work is to utilize machine learning methods to recognize pathological speech, particularly dysphonia. We extracted 1560 speech features and used these to train the classification model. As classifiers, three state-of-the-art methods were used: K-nearest neighbors, random forests, and support vector machine. We analyzed the performance of classifiers with and without gender taken into acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The SVM classifier achieved the highest accuracy by reducing the feature set to 300 using the filter FS method in the original 1560 feature. The overall classification performance based on feature selection was the highest, with 80.3% for mixed samples, 80.6% for female samples, and 86.2% for male samples [13].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The SVM classifier achieved the highest accuracy by reducing the feature set to 300 using the filter FS method in the original 1560 feature. The overall classification performance based on feature selection was the highest, with 80.3% for mixed samples, 80.6% for female samples, and 86.2% for male samples [13].…”
Section: Related Workmentioning
confidence: 99%
“…As a field of study, pathological voice signal processing has always aimed to create objective and accurate classifications of voice disorders. Additionally, there have been many contributions that focus on various aspects of speech processing from feature extractions to decision support systems based on deep learning methods [13][14][15][16][17][18][19]. This section provides a brief overview of several recent findings related to the research topic of this paper.…”
Section: Related Workmentioning
confidence: 99%
“…In the model, this forces much more variance among the trees and eventually results in less correlation between trees. Therefore, trees that are not only learned on different sets of data (bagged) but also use different features will make decisions eventually [20,21]. The typical steps to be followed for the core working of RF are;…”
Section: ) Support Vectormentioning
confidence: 99%
“…Recently, machine learning (ML) and deep learning methods have been used to better predict voice disorders, achieving accuracy levels as high as 90% by using the acoustic parameters of jitter, shimmer, and noise-toharmonic ratio (NHR) 13 . Another study using Gaussian mixture model system reported discriminating vocal fold disorders with 99% accuracy 14 .…”
Section: Introductionmentioning
confidence: 99%